Observation of protonation-induced intra-molecular metal-to-metal charge transfer in cyano-bridged [Fe-CN-Mn/Ni] dinuclear complexes - Jia, Shuwen; Zhu, Xinrui; Li, Dongfeng (Dalton transactions : an international journal of inorganic chemistry, 2023)
A key challenge in the design of magnetic molecules with intramolecular charge transfer behavior is to obtain reversible magnetic bistability triggered by external stimuli. Here, we show that two dinuclear metal complexes, [(bbp)Fe(CN) 3 Mn(Py 5 Me 2 )]·2.5CH 3 OH ( 4 ) and [(bbp)Fe(CN) 3 Ni(Py 5 Me 2 )]·2.5CH 3 OH ( 5 ) (Py 5 Me 2 = 2,6-bis(1,1-di(pyridine-2-yl)ethyl)pyridine, H 2 bbp = 2,6-bis(benzimidazole-2-yl)pyridine), were self-assembly synthesized by (Bu 4 N) 2 [(bbp)Fe III (CN) 3 ] and [Mn(Py 5 Me 2 )(OH 2 )](ClO 4 ) 2 or [Ni(Py 5 Me 2 )(OH 2 )](ClO 4 ) 2 , respectively. Complexes 4 and 5 exhibited intramolecular metal-to-metal charge transfer with the addition of acids or bases in solution by UV-visible spectrophotometric measurements and electrochemistry studies, and concomitant switching of the {Fe III (μ-CN)Mn II /Ni II } state to the {Fe II (μ-CN)Mn III /Ni III } state. The possibility of external stimulus induced intra-molecular metal-to-metal charge transfer by protonation in [(bbp)Fe(CN)3Mn(Py5Me2)]·2.5CH 3 OH and [(bbp)Fe(CN)3Ni(Py5Me2)]·2.5CH 3 OH molecules was investigated.